An Efficient, High Power Q-Band SiGe HBT Power Amplifier with A Compact Four-Way Wilkinson Power Combiner Balun for Emerging Very Low-Earth-Orbit SATCOM - Lee, Hanjung; Han, Insu; Hwang, Jaehyeon; Ju, Inchan (Digest of Papers - IEEE Radio Frequency Integrated Circuits Symposium, 2024)
This work presents an energy-efficient, high power Q-band SiGe HBT cascode power amplifier (PA). A novel four-way Wilkinson power combiner balun (WPCB), realized by two coupled line impedance inverting baluns, is proposed not only to simplify signal routing for compact size, but also to obtain efficient power combining with an excellent signal balance. A prototype Q-band PA attains measured peak Pout, peak PAE, and power gain of 24.0 dBm, 35.3%, and 23.0 dB at 43.0 GHz, respectively, the highest power density among any Q-band Sibased PAs. Its 1 dB Pout bandwidth (BW) ranges from 37.0 to 43.0 GHz, covering downlink of Very Low Earth orbit (VLEO) satellite communication (SATCOM). The PA delivers Pavg of 18.1 dBm with PAEavg of 21.0% at 250MHz symbol rate DVB-S2X 64 APSK modulation.
Keywords: Balun; BiCMOS; High power; LEO; Power amplifier; Q-bands; Satellite communication; Satellite communications; SiGe HBTs; Wilkinson; Balun; BiCMOS; HBT; LEO; power amplifier (PA); satellite communication (SATCOM); SiGe; Wilkinson